2019
DOI: 10.3390/ani9040189
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Safety Assessment of Feed Streams for Black Soldier Fly Larvae: A Case Study with Aquaculture Sludge

Abstract: The production of food is an intensive source of environmental impact. In aquaculture, one source of impact is solid waste, which contains high concentrations of minerals, other nutrients, and metals. The larvae of Hermetia illucens are capable of consuming this material, but applying technology that is based on these larvae for managing waste streams, like those from aquaculture, requires careful examination of safety risks. A study is performed examining the growth performance of larvae that were fed on soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 37 publications
(54 reference statements)
5
56
2
Order By: Relevance
“…There is a growing interest in utilization of live black soldier fly larvae for feeding poultry. Literature indicates that these insects are nutritious and their farming could facilitate circular economy [20]. Moreover, these insects could also help in solving some welfare issues related to poultry farming, e.g., feather pecking [43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a growing interest in utilization of live black soldier fly larvae for feeding poultry. Literature indicates that these insects are nutritious and their farming could facilitate circular economy [20]. Moreover, these insects could also help in solving some welfare issues related to poultry farming, e.g., feather pecking [43].…”
Section: Discussionmentioning
confidence: 99%
“…This scenario indicates the urgent need to find soy meal substitute. Insects could be grown using wide range of agro-food industry by-products, serving as an important pillar of local circular economy [20]. From the outcomes of this study it is suggested that live Hermetia illucens larvae (in addition to other plant protein sources) could be successfully used for the replacement of soy in European poultry diets without detrimental effects on production performance, behavior and welfare of older layer hens.…”
Section: Effect On Production Performancementioning
confidence: 91%
See 2 more Smart Citations
“…75 H. illucens could be grown on a wide range of organic side streams and contributes to a circular economy. 76,77 Exoskeletons from H. illucens larvae contain up to 35% chitin, 78 which means that it is one of the main compounds that could be isolated from the byproducts of the insect farming industry. 73 Thus, chitin-rich byproducts from insect farming present a new and sustainable source of commercial chitin.…”
Section: Introductionmentioning
confidence: 99%